Kajian Semiotika Maskot City Branding Kota Malang Pada Media Official Website OSIDANJI.COM - muhammad Daniel Septian (Program Pendidikan Vokasi Universitas Brawijaya, 2018)
City Branding is ane of efforts to compete in this globalization era. Regarding this, Malang City has done an effort of pictorial mark or brand identity by using mascot. Mascot can display interesting visuals and give meaning in accordance with the purpose of the city branding of Malang city. The mascot which was inaugurated last December is expected to represent the vision of the city branding concept of Malang City. However, some parties are still questioning the suitability of the mascot as a reflection of the people of Malang. Some argue that the color of this mascot resembles the color of the mascot of the football club Surabaya Persebaya. To examine this mascot deeper, this study uses the Semiotics method in assessing the implicit signs of the mascot. Semiotic theory used is the theory of Roland Barthes in dissect sign codes. Then the sample of visual mascot was downloaded from the official website maskot malang, namely Osidanji.com. The findings show that the figure of lions and birds of war on the mascot is considered appropriate because the lion as a leader is considered capable of being a role model for cities in eastern Java. Furthermore, the green color used in the mascot has nothing to do wuth the sign of Persebaya. The meaning of the green color of the mascot implies beauty, fertility and hospitality.